2020
DOI: 10.1371/journal.pone.0228765
|View full text |Cite
|
Sign up to set email alerts
|

The health status of transgender and gender nonbinary adults in the United States

Abstract: The goal of this exploratory study was to delineate health differences among transgender subpopulations (transgender women/TW, transgender men/TM, gender nonbinary/GNB adults). 2015 Behavioral Risk Factor Surveillance System data were analyzed to compare the health of three groups (TW:N = 369; TM:N = 239; GNB:N = 156). Logistic regression and adjusted odds ratios were used to determine whether health outcomes (fair/poor health, frequent physical and mental unhealthy days, chronic health conditions, and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 60 publications
2
40
1
1
Order By: Relevance
“…Such studies are failing to define sex and gender as non-binary variables when studying the health of populations. 164 , 165 Among studies that reported race and/or ethnicity, data were collected from different sources ranging from medical records to self-report. The COVID-19 pandemic underscored the importance of calculating race and ethnic-specific incidence of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are failing to define sex and gender as non-binary variables when studying the health of populations. 164 , 165 Among studies that reported race and/or ethnicity, data were collected from different sources ranging from medical records to self-report. The COVID-19 pandemic underscored the importance of calculating race and ethnic-specific incidence of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to honor this distinction while also allowing for individuals who reported being both men and women to transcend the transfeminine versus transmasculine binary. Second, our survey presented a limited number of gender options to an audience from multiple countries in which being a third gender (e.g., two-spirit, bissu, fa’afafine) is distinct from many Western concepts of being transgender [ 34 37 ]. Lastly, in line with recommendations from Restar et al, we saw statistically significant differences when comparing nonbinary individuals with transmasculine and transfeminine individuals [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…We wanted to honor this distinction while also allowing for individuals who reported being both men and women to transcend the transfeminine versus transmasculine binary. Second, our survey presented a limited number of gender options to a global audience in which being a third gender (e.g., two-spirit, bissu, fa’afafine, qariwarmi) is distinct from many Western concepts of being transgender 33 . Lastly, in line with recommendations from Restar et al, we saw statistically significant differences when comparing non-binary individuals with transmasculine and transfeminine individuals 34 .…”
Section: Methodsmentioning
confidence: 99%